Coefficients bounds on a certain class of multivalent analytic functions / Laxmipriya Parida and Ashok Kumar Sahoo - Parida, Laxmipriya; Sahoo, Ashok Kumar (Unit Penerbitan, UiTM Kelantan, 2022)
In the present work a sub-class Rbp,n (a1,c1,S,T) of f∈Ap(n) is defined by using a linear operator Lp (a1,c1) and obtained sufficient condition in terms of the coefficients of f∈Ap(n) to be a member of this class. Furthermore, the Fekete-Szego problem is completely solved and found that the functional |ap+3ap+1-a2p+2 | is bounded. Finally, the sharpness of the associated estimates is also studied.